A system to investigate and adjust profile pattern of computed tomography dose index along the longitudinal-axis - Anam, Choirul; Amilia, Riska; Naufal, Ariij; Dwihapsari, Yanurita; Dougherty, Geoff (Intelektual Pustaka Media Utama, 2023)
The purpose of this study to develop software to extract and investigate the rofiles of the tube current and volume computed tomography dose index (CTDIvol) along the longitudinal axis (z-axis). The tube current and CTDIvol were extracted from the Digital Imaging and Communications in Medicine (DICOM) header of every image along the longitudinal axis. We evaluated the profiles of the tube current and CTDIvol from eight computed tomography (CT) scanners. If the CTDIvol did not fluctuate along the fluctuation of the tube currents, then the system will adjust the CTDIvol with tube currents. It is found that TCM is not always activated. If TCM is activated, the profiles of TCM vary from one scanner to another. The Siemens and Philip scanners have adjusted the CTDIvol profile with tube current, but the Toshiba scanner has not. By developed software, CTDIvol profile of the Toshiba can be easily adjusted. In conclusion, software to investigate the profile pattern of CTDIvol along the longitudinal axis has been successfully developed. The software is easy to use and works quickly. From this study, medical staff must be careful when using the CTDIvol along longitudinal axis contained in each DICOM header.